One must reconstitute the functions of interest from purified proteins - Spudich, James A. (Frontiers in Physiology, 2024)
I am often asked by students and younger colleagues and now by the editors of this issue to tell the history of the development of the in vitro motility assay and the dual-beam single-molecule laser trap assay for myosin-driven actin filament movement, used widely as key assays for understanding how both muscle and nonmuscle myosin molecular motors work. As for all discoveries, the history of the development of the myosin assays involves many people who are not authors of the final publications, but without whom the assays would not have been developed as they are. Also, early experiences shape how one develops ideas and experiments, and influence future discoveries in major ways. I am pleased here to trace my own path and acknowledge the many individuals involved and my early science experiences that led to the work I and my students, postdoctoral fellows, and sabbatical visitors did to develop these assays. Mentors are too often overlooked in historical descriptions of discoveries, and my story starts with those who mentored me.